ANALYSIS OF IMPORT-EXPORT TRENDS AND MARKET INTEGRATION OF RICE IN ASEAN-5 IN 2017.1 - 2021.12 - Novita Dea Asmarawati; Hastuti, Sri Rahayu Budi (Universitas Islam Negeri Alauddin Makassar, 2024)
Rice plays an important role in the economic, social, and political stability of ASEAN. The presence of the ASEAN Economic Community (AEC) in 2015 shows that market integration in ASEAN is becoming more real. The objective of this study is to analyze trends in rice imports and exports in ASEAN, integration of rice markets, causality relationships, and impulse response based on rice prices in the ASEAN. Data used include annual data on import and export of rice from Indonesia, Malaysia, the Philippines, Thailand, and Vietnam in 2000-2021 as well as monthly data on rice price in 2017.1 - 2021.12. The methods used are trend analysis, Johansen cointegration test, Vector Autoregression (VAR) estimate with Vector Error Correction Model (VECM), Granger causality test, and impulse response analysis. The result is that the trend pattern of rice imports in Indonesia tends to decrease, while the trend of imports to Malaysia and the Philippines as well as exports to Thailand and Vietnam rises every year. There is integration of the rice market in ASEAN as well as a pattern of coherent and reciprocal inter-national causal relations. Keywords: rice, market integration, ASEAN and VECM